Humanity unmasked - Scott, Stanley James, author; Dormer, James T., advisor; Simons, Stephen R., advisor; Beachy-Quick, Dan, 1973-, committee member; Flippen, Paul, committee member; Lehene, Marius, committee member (Colorado State University. Libraries, 2009)
The darker facets of human nature drive my work. The figures you see in these prints and drawings are very real depictions of, and responses to, internal conflict. These figures offer the viewer a deeper level of understanding of the human condition as present both within the artist and society as a whole. I am particularly interested in the elements that make us uncomfortable and the aspects of ourselves we deny. These unexpressed emotions are the source of the tension in the images. The tension that binds each of these figures is inside us, driving our own actions and choices. I feel we need to accept and acknowledge our inner demons, both at an individual and a societal level. My work accepts this internal conflict as a normal part of the human condition that we all feel when we struggle. By speaking honestly through the works, the viewer is challenged to redefine their relationship to the internal struggle invoking a raw response.
Keywords: printmaking; drawing